Multivariate guard-bands and total risk assessment on multiparameter evaluations with correlated and uncorrelated measured values - Cintia Margueiro da Silva; Felipe Rebello Lourenço (Universidade de São Paulo, 2024)
Abstract The quality, efficacy, and safety of medicines are usually verified by analytical results. Measurement uncertainty is a critical aspect for the reliability of these analytical results. The pharmacopeial compendia usually adopt a simple acceptance rule that does not consider information from measurement uncertainty. In this work, we compared decision-making using simple acceptance and decision rules with the use of guard-band for multiparameter evaluation of ofloxacin ophthalmic solution and acyclovir topical cream. Ciprofloxacin ophthalmic solution and acyclovir topical cream samples were subject to pharmacopeial tests and assays. Multivariate guard-band widths were calculated by multiplying the standard uncertainty (u) by an appropriate multivariate coverage factor (k'). The multivariate coverage factor (k') was obtained by the Monte Carlo method. According to the simple acceptance rule, all the results obtained for ciprofloxacin ophthalmic solution and acyclovir topical cream are within the specification limits. However, the risk of false conformity decisions increases for ciprofloxacin tests. Decisions made using the simple acceptance rule and decision rules with the use of guard-band may differ. The simple acceptance rule may increase the risk of false conformity decisions when the measured value is close to the regulatory specification limits and/or when the measurement uncertainty value is inappropriately high. Nevertheless, the guard-band decision rule will always reduce the risk of false conformity decisions. Therefore, using information on measurement uncertainty in conformity assessment is highly recommended to ensure the proper efficacy, safety, and quality of medicines.